تأهيل رأس المال الفكري وأهميته في تحقيق القدرة التنافسية للمؤسسات الصناعية (Journal of Economics and Management Research, 2020)
تتحدد مشكلة الدراسة في افتقار الكثير من المؤسسات الوطنية إلى امتلاك تصور استراتيجي عن أثر الاستثمار في رأس المال الفكري في نشاطها، وفي درجة ومستوى ذلك التأثير، مما يحتم عليها أن تغيّر منه استجابة لمتطلبات المتغيرات الاقتصادية الراهنة، وتعتمد فاعليته على مدى التأثير الذي يحدثه. وتأتي أهمية هذه الدراسة كونها تتناول بالوصف والتحليل في تبيان أهم التحديات التي فرضتها الظروف الاقتصادية على المؤسسات الوطنية، تقرر مدى نجاحها وسط بيئة تنافسية تستلزم منها تأهيل رأس المال الفكري وزيادة كفاءته. وأن أي جهد يوجه نحو تعميق المعرفة العلمية والعملية في إدارة رأس المال الفكري هو نشاط مبتكر ينتج قيمة مضافة. The problem of the study is determined in the lack of many national institutions to possess a strategic vision of the impact of investing in intellectual capital on their activities, and in the degree and level of that influence, which necessitates them to change from it in response to the requirements of the current economic variables, and its effectiveness depends on the extent of the impact it has. The importance of this study stems from the fact that it deals with description and analysis in showing the most important challenges imposed by economic conditions on national institutions, which determine the extent of their success in a competitive environment that requires them to rehabilitate intellectual capital and increase its efficiency. And that any effort directed towards deepening scientific and practical knowledge in the management of intellectual capital is an innovative activity that produces added value.